The phenomenon of occupational burnout and the need for its regulation in Polish Labor Law - Ficner, Aleksandra; Szymanowski, Adrian (Undesirable Phenomena in Employment from the Perspective of Labour Law - Selected Issues, 2023)
The article deals with the issue of the concept of occupational burnout. The work includes aspects of foreign solutions related to this term, as well as de lege ferenda postulates in the field of Polish labor law regulations relating to pathologies in the work environment that can lead to professional burnout.